2006
DOI: 10.5005/jcdp-7-1-71
|View full text |Cite
|
Sign up to set email alerts
|

A One-Year Clinical Evaluation of a High-Viscosity Glass Ionomer Cement in Primary Molars

Abstract: In this study one-year clinical results of high-viscosity glass ionomer cement (GIC) (Fuji IX, A3, GC, Japan) were determined in class I and class II restorations in 68 primary molars with occlusal or approximal caries. Following caries removal and cavity preparation, the teeth were restored with Fuji IX. The restorations were evaluated according to the U.S. Public Health Service's (USPHS) criteria at the end of one year. Statistical analyses of the data obtained were analyzed using the X 2 test. The evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
5
3
1
Order By: Relevance
“…Regarding the results of secondary caries, score A was shown in 87.1% and 74.2% among Fuji II and Fuji IX restorations respectively (Table 3 and Figure 8), whereas score B (secondary caries) was noted in 12.9% and 25.8% of Fuji II and Fuji IX restorations respectively after 12 months. Such results disagreed with the results of Yilmaz et al, 2006 (37) in which the recorded secondary caries was 2.9% when Fuji IX was used. Further, the results of this study disagreed likewise with study conducted by Daou et al, 2008 (35) in which 3% and 12% of the evaluated restorations had evidence of secondary caries when restored by Fuji II and Fuji IX respectively.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Regarding the results of secondary caries, score A was shown in 87.1% and 74.2% among Fuji II and Fuji IX restorations respectively (Table 3 and Figure 8), whereas score B (secondary caries) was noted in 12.9% and 25.8% of Fuji II and Fuji IX restorations respectively after 12 months. Such results disagreed with the results of Yilmaz et al, 2006 (37) in which the recorded secondary caries was 2.9% when Fuji IX was used. Further, the results of this study disagreed likewise with study conducted by Daou et al, 2008 (35) in which 3% and 12% of the evaluated restorations had evidence of secondary caries when restored by Fuji II and Fuji IX respectively.…”
Section: Discussioncontrasting
confidence: 93%
“…In other words, score A (absence of marginal discoloration) was noted in 67.7% and 38.7% when Fuji II and Fuji IX were used respectively. This was in contrast to results of Folwaczny et al, 2000 (39) and Yilmaz et al, 2006 (37) in which B score (marginal discoloration) was noted in 17.6% when Fuji II was used in the former study and 14.7% was revealed when Fuji IX was applied in the latter study. In addition, the results of this study disagreed with results of study conducted by Daou et al, 2008 (35) where no marginal discoloration was observed when Fuji II was used after 12 months.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The powder–liquid ratios were higher than earlier conventional restoratives. [ 3 ] Improved characteristics include the adhesion, fast setting, ion exchange, high levels of compressive, flexural and tensile strength, surface hardness, high abrasion resistance, and fluoride release. However, these HVGIC's still have many disadvantages such as final polishing, which can be done only after 24 hours, short working time and slow development of ultimate properties, moisture dehydration resulting in micro-cracks, and less cohesive strength as compared to the resin cements.…”
Section: Introductionmentioning
confidence: 99%
“…6 Conventional glass ionomer was used as a sealant of pit and fissure of erupted permanent molar tooth. [7][8][9] It is biocompatible with the pulpal tissue, and it has the ability to chemically bond to the tooth tissue and it has almost similar co-efficient of thermal expansion to that of tooth structure and ability to fluoride release. 10 However, its low physical and mechanical strength, moisture sensitivity during the initial setting time, poor wear resistance, loss of anatomic form or marginal adaptation limit their use in load bearing areas.…”
Section: Introductionmentioning
confidence: 99%